Вопрос:

Вычислите (27*3^(-6))^2*(9^(-1))^(-2).

Ответ:

\[\left( 27 \cdot 3^{- 6} \right)^{2} \cdot \left( 9^{- 1} \right)^{- 2} =\]

\[= \left( 3^{3} \cdot 3^{- 6} \right)^{2} \cdot \left( \left( 3^{2} \right)^{- 1} \right)^{- 2} =\]

\[= \left( 3^{- 3} \right)^{2} \cdot \left( 3^{- 2} \right)^{- 2} = 3^{- 6} \cdot 3^{4} =\]

\[= 3^{- 2} = \left( \frac{1}{3} \right)^{2} = \frac{1}{9}\]

Похожие

© 2021 Copyright. Все права защищены. Правообладатель SIA Ksenokss.
Адрес: 1069, Курземес проспект 106/45, Рига, Латвия.
Тел.: +371 29-851-888 E-mail: [email protected]